ELEVATED FUNCTIONAL CONNECTIVITY ALONG A CORTICOSTRIATAL LOOP AND THE MECHANISM OF AUDITORY/VERBAL HALLUCINATIONS IN PATIENTS WITH SCHIZOPHRENIA - Hoffman, Ralph E. (2010)
BACKGROUND: Higher levels of inter-region functional coordination can facilitate emergence of neural activity as conscious percepts. We consequently tested the hypothesis that auditory/verbal hallucinations (AVHs) arise from elevated functional coordination within a speech processing network. METHODS: Functional coordination was indexed using functional connectivity (FC) computed from functional magnetic resonance imaging data. Thirty-two patients with schizophrenia reporting AVHs, 24 similarly diagnosed patients without hallucinations, and 23 healthy controls were studied. FC was seeded from a bilateral Wernicke’s region delineated according to activation detected during AVHs in a prior study. RESULTS: Wernicke’s-seeded FC with Brodmann Area 45/46 of the left IFG was significantly greater for hallucinating patients compared to nonhallucinating patients, but not compared to healthy controls. In contrast, Wernicke’s-seeded FC with a large subcortical region that included the thalamus, midbrain and putamen was significantly greater for the combined patient group compared with healthy controls after false discovery rate correction, but not when comparing the two patient groups. Within that subcortical domain, the putamen demonstrated significantly greater FC relative to a secondary left IFG seed region when hallucinators were compared to nonhallucinating patients. A follow-up analysis found that FC summed along a loop linking the Wernicke’s and IFG seed regions and the putamen was robustly greater for hallucinating patients compared to nonhallucinating patients and healthy controls. CONCLUSIONS: These findings suggest that higher levels of functional coordination intrinsic to a corticostriatal loop comprise a causal factor leading to AVHs in schizophrenia.